Treatment of bulky lymph nodes in locally advanced cervical cancer: boosting versus debulking. Issue 7 (28th April 2022) - Olthof, Ester Paulien; Wenzel, Hans; van der Velden, Jacobus; Spijkerboer, Anje M; Bekkers, Ruud; Beltman, Jogchum J; Nijman, Hans W; Slangen, Brigitte; Smolders, Ramon; van Trommel, Nienke; Zusterzeel, Petra L M; Zweemer, Ronald; et al.
Abstract : Objective: Treatment strategies for bulky lymph nodes in patients with locally advanced cervical cancer scheduled for definitive chemoradiation include nodal boosting with radiotherapy, surgical debulking, or both. The aim of this retrospective cohort study was to compare survival and toxicity in patients receiving these treatments and to compare them with a group that received neither form of treatment. Methods: Women diagnosed between January 2009 and January 2017 with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IB2, IIA2–IVA cervical cancer with lymph nodes ≥1.5 cm without upper limit on pretreatment imaging and treated with definitive chemoradiation were selected from the Netherlands Cancer Registry. Patients were categorized by intention-to-treat strategy: boosting, debulking, or neither treatment, with subgroup analysis for patients receiving both treatments, that is, debulking with boosting. Overall and relapse-free survival outcomes were compared by Kaplan-Meier and Cox regression analyses and toxicity by logistic regression analysis. Results: Of 190 patients, 101 (53%) received only nodal boosting, 31 (16%) debulking alone, 29 (15%) debulking combined with boosting, and 29 (15%) received neither treatment. The 5 year overall and relapse-free survival for the treatment groups were 58%, 45% and 45% (p=0.19), and 47%, 44% and 46% (p=0.87), respectively. Multivariable Cox regression analyses demonstrated no differences in overall and relapse-free survival. Combination of debulking with boosting was associated with decreased overall and relapse-free survival compared with debulking alone (HR 2.47, 95% CI 1.22 to 5.00; and HR 2.37, 95% CI 1.14 to 4.93). Nodal boosting was independently associated with a decreased toxicity risk compared with debulking strategy (OR 0.37, 95% CI 0.16 to 0.83). Conclusions: This study showed no survival benefit from either nodal boosting or debulking strategy in patients with suspicious bulky nodes. Nodal boosting might, however, be associated with less toxicity. Dual treatment with debulking and boosting showed a worse survival outcome because this group probably represents patients with poor prognostic factors.